Centrality and transverse momentum dependence of D0-meson production at mid-rapidity in Au+Au collisions at √sNN=200GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physical review, 2019)
We report a new measurement of D0-meson production at mid-rapidity (|y|<1) in Au + Au collisions at √sNN=200GeV utilizing the heavy flavor tracker, a high resolution silicon detector at the STAR experiment. Invariant yields of D0 mesons with transverse momentum pT≲9GeV/c are reported in various centrality bins (0-10%, 10-20%, 20-40%, 40-60%, and 60-80%). Blast-wave thermal models are used to fit the D0-meson pT spectra to study D0 hadron kinetic freeze-out properties. The average radial flow velocity extracted from the fit is considerably smaller than that of light hadrons (π,K, and p), but comparable to that of hadrons containing multiple strange quarks (ϕ,Ξ−), indicating that D0 mesons kinetically decouple from the system earlier than light hadrons. The calculated D0 nuclear modification factors reaffirm that charm quarks suffer a large amount of energy loss in the medium, similar to those of light quarks for pT>4GeV/c in central 0-10% Au + Au collisions. At low pT, the nuclear modification factors show a characteristic structure qualitatively consistent with the expectation from model predictions that charm quarks gain sizable collective motion during the medium evolution. The improved measurements are expected to offer new constraints to model calculations and help gain further insights into the hot and dense medium created in these collisions.
Gesehen am 28.05.2018
0 hinter D ist hochgestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 28.05.2019